1992
DOI: 10.5032/jae.1992.02034
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Issues: Farmers' Perceptions About Usefulness Of Informational And Orgranizational Sources

Abstract: The public, governmental agencies and the scientific community have recently expressed concerns about the effects of agricultural practices on the environment and the quality of life in general. During the past several years, numerous researchers have attempted to address these and related concerns. However, most of the proposed solutions address the effects of agricultural practices on the environment rather than the solutions to such problems through educational efforts. Perhaps the most important factor oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 6 publications
1
12
1
1
Order By: Relevance
“…The results support previous literature showing that the best way to communicate with producers is through a variety of communication channels (Boone & Zenger, 2001;Bruening et al, 1992;Creswell, 1990;Dollisso & Martin, 1999;Kotile & Martin, 2000;Lasley et al, 2001;Richardson & Mustian, 1994;Rollins et al, 1991;Suvedi et al, 1999;Trede & Whitaker, 1998). Extension educators and communicators should target the use of communication methods discussed in this study according to how producers use each method (Bouare & Bowen, 1990;Radhakrishna et al, 2003;Richardson & Mustian, 1994;Rollins, 1993).…”
Section: Discussionsupporting
confidence: 87%
“…The results support previous literature showing that the best way to communicate with producers is through a variety of communication channels (Boone & Zenger, 2001;Bruening et al, 1992;Creswell, 1990;Dollisso & Martin, 1999;Kotile & Martin, 2000;Lasley et al, 2001;Richardson & Mustian, 1994;Rollins et al, 1991;Suvedi et al, 1999;Trede & Whitaker, 1998). Extension educators and communicators should target the use of communication methods discussed in this study according to how producers use each method (Bouare & Bowen, 1990;Radhakrishna et al, 2003;Richardson & Mustian, 1994;Rollins, 1993).…”
Section: Discussionsupporting
confidence: 87%
“…Bruening (1991) reported Iowa farmers also preferred field demonstrations and county and local meetings as useful communication methods when learning about environmental issues. In a later study by Bruening, Radhakrislma, and Rollins (1992), the same preference was shown by Pennsylvania farmers for methods including demonstrations, tours, or on-farm consults when seeking to learn information about the environment. The least favored methods were those with minimal interaction, for example home study or computer assisted instruction.…”
Section: Interpersonalmentioning
confidence: 88%
“…However, the diversity in personal beliefs and value systems of individual extension educators may potentially define individual convictions, perceptions, attitudes and behaviors (Schauber 2001). The importance of perceptions in relation to attitudes towards major agricultural issues is reflected by the number of studies that have been conducted globally in agricultural education (Blezek and Dillon 1991;Bruening, Radhakrishna and Rollins 1992;Chizari, Lindner and Zoghie 1999;Farouque and Takeya 2007).…”
Section: The Theoretical and Conceptual Frameworkmentioning
confidence: 99%